2009
DOI: 10.1364/oe.17.003980
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of post-glaucoma-surgery structures by three-dimensional and polarization sensitive anterior eye segment optical coherence tomography

Abstract: A sequential case series of post-glaucoma-surgery structures examined by three-dimensional corneal and anterior eye segment optical coherence tomography (3D-CASOCT) and 3D polarization sensitive CASOCT (PS-CASOCT) is presented. A total of 5 patients who underwent glaucoma surgery were included in this study. Of these, 1, 1, and 3 patient underwent trabeculotomy, laser iridotomy, and trabeculectomy respectively. One patient each who had undergone trabeculotomy or laser iridotomy was examined using a prototype 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…PS-OCT has been used to measure birefringence of cornea [19], trabecular meshwork [20], retinal nerve fibers [21][22][23], and scarred tissue of age-related macular degeneration [24]. PS-OCT has also been used to investigate birefringence of pterygium and scarred tissue of the conjunctiva after trabeculectomy [25,26]. Although it is known that the sclera has high birefringence in both the anterior and posterior segments of the eye [27][28][29], the association of scleral birefringence with ocular diseases has not been investigated to date except in one case study of necrotizing scleritis [30].…”
Section: Introductionmentioning
confidence: 99%
“…PS-OCT has been used to measure birefringence of cornea [19], trabecular meshwork [20], retinal nerve fibers [21][22][23], and scarred tissue of age-related macular degeneration [24]. PS-OCT has also been used to investigate birefringence of pterygium and scarred tissue of the conjunctiva after trabeculectomy [25,26]. Although it is known that the sclera has high birefringence in both the anterior and posterior segments of the eye [27][28][29], the association of scleral birefringence with ocular diseases has not been investigated to date except in one case study of necrotizing scleritis [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been difficult to diagnose the functioning of the bleb using the conventional imaging methods. PS-OCT may be able to diagnose the scar tissue after the surgery [17].…”
Section: Introductionmentioning
confidence: 99%
“…Bleb appearance has been assessed using slit-lamp biomicroscopy [1][2][3], ultrasound biomicroscopy (UBM) [4][5][6][7][8], and optical coherence tomography (OCT) [9][10][11][12][13][14][15][16][17][18]. Picht and Grehn [1] reported that trabeculectomy is more likely to have a better outcome if the filtering bleb appears on slit-lamp biomicroscopy to have more microcysts, fewer conjunctival and corkscrew vessels, is not encapsulated, and is lower in height.…”
Section: Introductionmentioning
confidence: 99%